PENERAPAN NILAI-NILAI PENDIDIKAN KARAKTER DALAM TARI GANDRUNG KREASI BANYUWANGI PADA SISWA DI SMA NEGERI 1 TEGALDLIMO - Hela Anggraini; I Nyoman Natajaya; I Wayan Lasmawan (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2022)
This study aims to determine the application of character education values ​​in Banyuwangi's gandrung creation rates to students at SMA Negeri 1 Tegaldlimo. This research is descriptive qualitative. The subjects of this study were the teacher of Banyuwangi's gandrung dance and students of SMA Negeri 1 Tegaldlimo. The data were collected using observation techniques, interview techniques, and documentation techniques. Data were analyzed by descriptive technique with qualitative meaning. The results of this study indicate that the values ​​of character education contained in Banyuwangi's Gandrung dance include: (1) religious, (2) tolerance, (3) discipline, (4) hard work, (5) creative, (6) curiosity. know, (7) the spirit of nationalism, (8) love for the homeland, and (9) responsibility. The values ​​that are implemented by students in the context of learning regional culture, are in accordance with the Banyuwangi regional culture. Some of the obstacles in implementing the character values ​​in the Banyuwangi creation gandrung dance: 1) the schedule for the implementation of the gandrung creative dance activities often clashes with other extracurricular activities, 2) the lack of facilities and infrastructure to support the gandrung creation dance, 3) the delay in related information and the gandrung dance event, and 4) at least the fans of the creative gandrung dance extracurricular.